PERKEMBANGAN TEKNOLOGI DAN KOMUNIKASI DALAM PENDIDIKAN - Maretha Dewi Anggraeni; Roufatul Mucharromah; Bela Zain Taqiyya; Rizka Elan Fadilah; I Ketut Mahardika; Firdha Yusmar (FKIP e-PROCEEDING, 2022)
The development of technology and information is growing rapidly and influential in the world of education. The development of technology and information in learning is very helpful for teachers in utilizing technological facilities to prepare the learning process or when the learning process takes place. Therefore the importance of technological developments in education for students and educators. In learning, educators can deliver learning materials more easily accepted by students through the use of technology. Information and communication technology has a very important role in the learning infrastructure, such as teaching materials provided in digital formats that can facilitate the teaching and learning process, which can be done anytime and anywhere. The purpose of writing this article is to provide insight to the author about the importance of the development of technology and communication in education. The research method used in this article is a literature research method. The results of research from literature sources indicate that the influence of technological and communication developments is very strong for students and educators. In the sense that it can be seen that as technology and communication develop, the quality of educational learning will increase.